The Bishop Score as a Predictor of Labor Induction Success: A Systematic Review - Kolkman, Diny G. E.; Verhoeven, Corine J. M.; Brinkhorst, Sophie J.; van der Post, Joris A. M.; Pajkrt, Eva; Opmeer, Brent C.; Mol, Ben Willem J. (American Journal of Perinatology, 2013)
Objective To assess the ability of the Bishop score to predict the mode of delivery in women scheduled for induction of labor at term.Study Design We performed a systematic literature search of electronic databases from inception to July 2009. Studies reporting on both the Bishop score and the outcome of labor in women scheduled for induction of labor at term were eligible. We used a bivariate model to estimate a summary receiver operating characteristic (sROC) curve for the outcome cesarean delivery.Results We included 40 primary articles reporting on 13,757 women. Study quality was mediocre. The sROC curve of the Bishop score in the prediction of cesarean delivery indicated a poor predictive capacity. For the prediction of cesarean delivery, the sensitivity-specificity combinations were 47%-75%, 61%-53% and 78%-44% for the Bishop scores of 4, 5, and 6, respectively. For a Bishop score below 9, the sensitivity-specificity combination was 95%-30%.Conclusion The Bishop score is a poor predictor for the outcome of induced labor at term and should not be used to decide whether to induce labor or not.
Keywords: Bishop score; induction of labor; outcome of labor; prediction